Adjuvant chemotherapy followed by concurrent chemoradiation is associated with improved survival for resected stage I‐II pancreatic cancer - Sung Jun Ma; Gregory M. Hermann; Kavitha M. Prezzano; Lucas M. Serra; Austin J. Iovoli; Anurag K. Singh (Cancer Medicine)
Abstract Background This National Cancer Database (NCDB) analysis evaluates the clinical outcomes of postoperative chemotherapy followed by concurrent chemoradiation (C + CRT) compared to concurrent chemoradiation (CRT) alone or adjuvant chemotherapy alone (C) for resected pancreatic cancer. Methods The NCDB was queried for primary stage I‐II, cT1‐3N0‐1M0, resected pancreatic adenocarcinoma treated with adjuvant C, CRT, or C + CRT (2004‐2015). Patients treated with C + CRT were compared with those treated with C (cohort C) and CRT (cohort CRT). Baseline patient, tumor, and treatment characteristics were examined. Kaplan‐Meier analysis, multivariable Cox proportional hazards method, forest plot, and propensity score matching were used. Results Among 5667 patients, median follow‐up was 34.7, 45.2, and 39.7 months for the C, CRT, and C + CRT cohorts, respectively. By multivariable analysis for all patients, C and CRT had worse OS compared to C + CRT. Treatment interactions were seen among pathologically node‐positive disease. C + CRT was favored in 1‐3 and 4+ positive lymph node diseases when compared to C or CRT alone, but none of the treatment options were significantly favored in node negative disease. Using propensity score matching, 2152 patients for cohort C and 1774 patients for cohort CRT were matched. C + CRT remained significant for improved OS for both cohort C (median OS 23.3 vs 20.0 months) and cohort CRT (median OS 23.4 vs 20.8 months). Conclusion This NCDB study using propensity score matched analysis suggests an OS benefit for C + CRT compared to C or CRT alone following surgical resection of pancreatic cancer, particularly for patients with pathologically positive lymph nodes.